In such good company [compact disc, unabridged] : eleven years of laughter, mayhem, and fun in the sandbox - Burnett, Carol (Books on Tape : Random House Audio, 2016)
Get the best seat in the house as comedy legend Carol Burnett tells the hilarious behind-the-scenes story of her iconic weekly variety series, The Carol Burnett Show. For eleven glorious seasons the guests, sketches and cast antics made the show legendary. Burnett lays it all out for us, from the show's original conception to its evolution into one of the most beloved primetime programs of its generation, and to the last show.